Edukasi Berbasis Digital tentang Pengetahuan Pasien Penyakit Ginjal Kronis (PGK) Dengan Terapi Hemodialisis: Tinjauan Literatur - Ekawati Ekawati; Erna Melastuti; Suyanto Suyanto (Jurnal Ners, 2025)
In the era of technology, providing digital-based education through the concept of applications by displaying theories or videos is one of the many results of technological advances that can be used as an interesting means of health education. This literature review aims to see the effectiveness of digital-based education in increasing the knowledge of chronic kidney disease (CKD) patients with hemodialysis therapy. The design used is a literature review. The search for articles in this study was through online databases that can be accessed via Google Scholar, Science Direct, Scopus, Elseiver and PubMed using keywords and Boolean Operators. Based on the results of the review of 10 selected journals, it was concluded that interventions by providing digital-based education and applications can effectively increase the knowledge of chronic kidney disease (CKD) patients with hemodialysis therapy. It is hoped that the provision of digital-based education and this application can be developed and used by health institutions and patients.